Canadian French translation and linguistic validation of the health-related quality of life utility measure for pre-school children. (2nd November 2021) - Poder, Thomas G.; Guertin, Jason R.; Touré, Moustapha; Pratte, Gabrielle; Gauvin, Cheyenne; Feeny, David; Furlong, William; Camden, Chantal
ABSTRACT: Background: There is a need to perform a Canadian French translation and linguistic validation of the health-related quality of life utility measure for pre-school children (HuPS) conceptually equivalent to the original Canadian English version. Research design and methods: The translation process consisted of forward and back translations. The linguistic validation was performed with the parents of preschool children during face-to-face cognitive debriefing interviews. The whole process was done in accordance with academic standards and the guidance of the Food and Drug Administration (FDA) for patient-reported outcome instruments. Results: The results of back translations indicated that 89% of the sentences were identical or almost identical to the original English-language wording. The review of the back translations led to a change in 13 sentences out of 91 from the reconciled forward translation, while the linguistic validation process with 13 parents led to 14 additional changes. Preliminary reliability validation results indicate a Cronbach's alpha of 0.73. Conclusion: The translation and linguistic testing processes were successful in creating a valid HuPS in Canadian French (HuPS-CF). This translation should be the subject of reliability and validity studies in a wide variety of clinical and general populations before to use in research projects.